Targeting Liver Sinusoidal Endothelial Cells: An Attractive Therapeutic Strategy to Control Inflammation in Nonalcoholic Fatty Liver Disease - Wang, Xue-Kai; Peng, Zong-Gen (Frontiers in Pharmacology, 2021)
Nonalcoholic fatty liver disease (NAFLD), especially its advanced stage nonalcoholic steatohepatitis (NASH), has become a threatened public health problem worldwide. However, no specific drug has been approved for clinical use to treat patients with NASH, though there are many promising candidates against NAFLD in the drug development pipeline. Recently, accumulated evidence showed that liver sinusoidal endothelial cells (LSECs) play an essential role in the occurrence and development of liver inflammation in patients with NAFLD. LSECs, as highly specialized endothelial cells with unique structure and anatomical location, contribute to the maintenance of liver homeostasis and could be a promising therapeutic target to control liver inflammation of NAFLD. In this review, we outline the pathophysiological roles of LSECs related to inflammation of NAFLD, highlight the pro-inflammatory and anti-inflammatory effects of LSECs, and discuss the potential drug development strategies against NAFLD based on targeting to LSECs.